Complementary and Alternative Medicine Use and Adherence to Conventional Cancer Treatment in Meru County, Kenya - Kiraki Monicah Wambui; Gabriel Mbugua; Robert Kei Mburug; Catherine Gichunge (Open Access Health Scientific Journal, 2023)
Background: Non-communicable diseases (NCDs) are the leading cause of global mortality with cancer ranking among the top cause of death. Unfortunately, most of these deaths occur in developing countries due to delays in the diagnosis of the disease. Consequently, the use of complementary and alternative medicine (CAM) among cancer patients is on an upward trend hence adherence to conventional cancer treatment (CCT) is a major health concern.Methods: A cross-sectional study was carried out in a conventional cancer centre in Meru County. A researcher-administered questionnaire was used to obtain data from 117 consenting patients. Demographic data, clinical data, history of any use of CAM before and after cancer diagnosis and any side effects were obtained from the study participants. Data were analyzed using the Statistical Package of Social Sciences (SPSS).Results: There were more female (53.8%) participants, mainly married (59.8%), Christians (97.4%) with primary education and above (69%). Almost half of the participants (47.9%,) were using CAM. Most of the participants (85.7%) started using CAM after a cancer diagnosis. More than half of the respondents using CAM (52%) had disclosed to the HCP mainly to find out about drug-drug interaction risk (41.4%). Only one (1.8%) CAM user had withdrawn the CCT to use CAM due to dissatisfaction with conventional medicine.Conclusion: The use of CAM is complementary and not alternative to CCT and hence may not influence adherence to CCT among cancer patients in Meru County. However, there is a need to provide health education to cancer patients on the use of complementary medicine and analyze the outcomes of patients who use complementary medicine while on CCT